Album biograficzne zasłużonych Polaków i Polek wieku XIX. Warsztatowe studia przypadków - Kowalczuk, Urszula (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
The article proposes a new reading of Album biograficzne zasłużonych Polaków i Polek wieku XIX (1901–1903) [Biographic album of distinguished nineteenth-century Polish men and women (1901–1903)]. It is proven that this collection of characteristically designed biographies and an unusual collective biography is an important work of Polish humanities of the turn of the twentieth century that can be placed in relation to both Thomas Carlyle’s hero concept and Jacob Burckhardt’s postulates of the ‘anthropologisation of history’. The three selected biograms (Klaudyna Potocka’s by Aleksander Kraushar, August Hiacynt Dziarkowski’s by Józef Peszke and Adolf Pawiński’s by Jan Karol Kochanowski) are case studies allowing for the reconstruction of the dilemmas and text strategies each time specifying the biographer’s unique workshop and the techniques of uncovering it.